LEGAL ANALYSIS OF THE ROLE OF THE POLICE IN THE INVESTIGATION PROCESS OF UNAUTHORIZED MINING CRIMINAL ACTS (RESEARCH STUDY IN THE JURISDICTION OF THE BINTAN POLICE) - Pandapotan, Marganda (Jurnal Hukum Khaira Ummah, 2024)
This study examines the application of restorative justice in law enforcement of criminal acts of vandalism at Polresta Barelang, Batam City, especially in the Rempang case. In the context of Indonesian law, Polresta Barelang plays an important role in handling vandalism cases that are often related to social and agrarian conflicts. Restorative justice, which emphasizes the restoration of relationships between perpetrators, victims, and the community, is an approach that is increasingly being considered. This study aims to assess the effectiveness of the application of restorative justice in resolving conflicts, minimizing negative impacts, and creating an environment conducive to restorative justice. This study also identifies obstacles faced, such as social resistance and lack of specific regulations, and offers solutions to improve the application of restorative justice in the future. The results of the study indicate that the application of restorative justice can improve social harmony and reduce the potential for ongoing conflict, although it still requires clearer regulatory support and wider socialization to the community.